Revisiting the Death and Autopsy of King George II - Suzuki, Yota; DeAnda, Abe, Jr. (AORTA, 2021)
It is commonly accepted that King George II died of an acute aortic dissection. The origin of this association derives from retelling of the official autopsy performed by Dr. Frank Nicholls. While there is no doubt that King George II did have a Stanford Type A dissection, critical descriptions in the report point to a more likely cause of death.
Keywords: aortic dissection; coronary artery disease; ventricular rupture